WHAT ARE WE LEARNING ABOUT THE INTERSECTION OF HOUSING, HEALTH, AND SOCIAL SERVICES? REPORTS FROM NEW STUDIES. (11th November 2018) - Simon-Rusinowitz, L; Sanders, A
Abstract: "Housing plus services" programs view affordable housing as a platform to provide health and social services to help low-income, frail elders remain in community settings. This symposium will discuss four ongoing implementation and research projects addressing the intersection of housing, health, and social services. Robyn Stone will describe a national demonstration and evaluation of a housing plus services model funded by the Department of Housing and Urban Development (HUD). The Integrated Wellness in Supportive Housing initiative (IWISH), which started in October, 2017, is a three-year, seven-state project that includes 40 treatment and control group housing buildings to determine the types and mix of services that most contribute to seniors remaining in the community. Lori Simon-Rusinowitz will discuss a federal interagency collaboration among the Administration for Community Living, HUD, the Health Resources and Services Administration, and Department of Transportation working with IWISH to infuse services from these agencies into the treatment group buildings. Emily Greenfield and Ayse Akincigil will present findings from a national study investigating whether differences in healthcare expenditures among senior housing residents differ by the availability and types of onsite services, as well as individuals' degree of functional impairment. Allen Glicksman and colleagues will discuss a study investigating whether unmet need for home repair is associated with negative health related outcomes among elders in the Philadelphia area. Alisha Sanders, Director of LeadingAge's Center for Housing Plus Services, will be the discussant.